Development and validation of curriculum-based problem-solving MCQ classroom tests in mathematics - Purity V. Mata; Quennie Rose H. Abao; Roxanne Kaye S. Bihasa; Glenda N. Kiamco; Anna Marie C. Neiz (International Journal of Evaluation and Research in Education (IJERE), 2026)
Classroom assessment is a fundamental element in the teaching and learning process. The objective of this study is to determine the validity of the teacher-made multiple-choice questions (MCQs) used in General Education Course Mathematics in the Modern World (GEC-MMW). Employing a quantitative descriptive research design, four sets of teacher-made MCQ tests were developed and administered to over 500 students across two campuses of a state university. The tests underwent expert validation, tryouts, and analysis using difficulty index (DIF I), discrimination index (DI), distractor efficiency (DE) and reliability testing. Most items showed an average level of difficulty, acceptable to excellent DI, and functional distractors (FD), with reliability coefficients ranging from 0.54 to 0.78. Moreover, mean percentage scores ranged from 42.94 to 50.95 revealed below-average student performance. These findings confirm that the developed tests are valid, reliable, suitable for classroom assessment, and demonstrate that item analysis is essential for improving test quality, identifying learning gaps, and informing instructional decisions.